Biology of Saccular Cerebral Aneurysms: A Review of Current Understanding and Future Directions - Fennell, Vernard S.; Kalani, M. Yashar S.; Atwal, Gursant; Martirosyan, Nikolay L.; Spetzler, Robert F. (Frontiers in Surgery, 2016)
Understanding the biology of intracranial aneurysms continues to be a clinical quandary. How these aneurysms form, progress, and rupture are poorly understood. Growing evidence indicates that well-established risk factors play a critical role, along with immunologic factors, in the development and clinical outcomes of these lesions. Much of the expanding knowledge of the inception, progression, and rupture of intracranial aneurysms implicates inflammation as a critical mediator of aneurysm pathogenesis. As a result, therapeutic targets seeking to exploit this arm of aneurysm pathogenesis have been implemented, and many have shown promising outcomes.